A Structural Model of the Elder Career Skill Development - Vijucksana Hutanon วิจักษณา หุตานนท์; Suwanna Narkwiboonwong สุวรรณา นาควิบูลย์วงศ์ (Dusit Thani College Journal, 2018)
In 2030, Thailand will lead into an extremely elderly society, so knowledge development is important. The purpose of this article is to synthesize the causal factors of the elder career skill development. The methods are content analysis from theories and literatures as well as a focus group discussion with the 6 elderly people (trainees, trainers, and training administrators) for conduct causal model of the elder career skill development. The result shows that causal model of the elder career skill development has 5 components. 1) The individual characteristic includes perceived ability, benefit, and attitude. 2) The training design includes, training, trainer and content requirement. 3) The training environment includes technology, group, and fund support. 4) The individual motivation includes relationship, self-esteem, and increase income. 5) The career development includes training satisfaction, skills, and knowledge for career. This model leads to policy recommendation, conceptual framework for empirical study (Structural Equation Modeling: SEM), and increased knowledge in vocational science and the elderly career development in the future.